Metodologia de elaboração de base de informações para alocação negociada de água: aplicação ao Açude Arneiroz II - Oliveira Filho, Raimundo Lauro de (2013)
This study aimed to formatting a methodology for development of information base for negotiated allocation of water in order to support the decisions of watershed committees and management committees in the operations of reservoirs monitored by the Company Management of Water Resources - COGERH. The weir Arneiroz II, located in the basin of Alto Jaguaribe in Arneiroz municipality, state of Ceará, responsible for evergreening 113 km Jaguaribe river to the headquarters city Jucás, the reservoir was identified for conducting the above research, by have a complex dynamic of evergreening. The methodology for compiling the information base began validation of information supply and demand system comprising Weir Arneiroz II, data source and loss studies in perennial traffic along the route. Thus, it was concluded that, for this case study, the scenario for the transport of water that meets existing demands satisfactorily and efficiently, is by means of open or closed ducts, and not by direct perpetuation Jaguaribe river to the city of Jucás. The scenario presents evergreening as losses decreased guarantee the supply of water for at least three years of extreme drought, while the losses in transit represent 79 % of the average flow rate released by the weir Arneiroz II valve on an annual operation evergreening